Hegemony, 'common sense' and compromise : a neo-gramscian analysis of multilateralism in South Africa's post-apartheid foreign policy - Taylor, Ian (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2000.